Primeiro Registro de Afídeos (Hemiptera: Aphidoidea) em Carambola (Averrhoa carambola L.) no Brasil - Cunha, Suzan Beatriz Zambon da; Sousa e Silva, Carlos Roberto (EntomoBrasilis, 2016)
A carambola (Averrhoa carambola L.) árvore de origem Asiática foi introduzida no Brasil em 1817, desde então vem aumentando sua área de cultivo no país. A planta é atacada por poucos insetos como as moscas e percevejos. Este trabalho relata a presença de Aphis gossypii Glover em A. carambola pela primeira vez no Brasil. First Record of Aphids (Hemiptera: Aphididae) on Starfruit (Averrhoa carambola L.) in Brazil Abstract. The starfruit (Averrhoa carambola L.) has origin Asiatic and was introduced in Brazil in 1817, since then has increased its cultivation area in the country. The plant is attacked by few insects like flies and bugs. This work reports the presence of Aphis gossypii Glover on A. carambola for the first time in Brazil.